Prislovi v sinonimnem slovarju - Ahlin, Martin (Jezik in slovstvo, 2005)
The dictionary description of adverbs in the dictionary of synonyms poses some questions to Slovene lexicography which have not been answered so far. In the existing dictionaries, particularly adverbs formed from adjectives are mainly not semantically independent dictionary entries, but are usually illustrated as sub-entries to base adjectives with reference to their adjectival meaning. When determining and describing synonymous relations there is a need arising for an independent semantic description which takes into account adverbial categorisation. The article illustrates some examples of solving questions concerning this matter by juxtaposition lexicological findings about Slovene adverbs so far, with the demands posed by the treatment of synonymous adverbs in the dictionary of synonyms.
Keywords: Slovene; slovenščina; sinonimi; leksikografija; lexicography; prislov; slovarji; sinonimni slovarji